2018
DOI: 10.1016/j.apsusc.2017.12.086
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure, charge transfer, and intrinsic luminescence of gadolinium oxide nanoparticles: Experiment and theory

Abstract: The cubic (c) and monoclinic (m) polymorphs of Gd 2 O 3 were studied using the combined analysis of several materials science techniques -X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), and photoluminescence (PL) spectroscopy. Density functional theory (DFT) based calculations for the samples under study were performed as well. The cubic phase of gadolinium oxide (c-Gd 2 O 3 ) synthesized using a precipitation method exhibits spheroidal-like nanoclusters wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…The shoulder of Zn 2p in Figure 5 c is centered at 1019.27 eV and can be associated with the Zn broken bonds or O vacancies [ 39 , 40 ]. Additionally, the peak at 139.6 eV appearing in the Gd 4d spectra can be ascribed to the Gd4d 5/2 , showing that the oxidation state of Gd ions in the NPs is +3, which exist in the form of Gd 2 O 3 [ 41 ]. The detectable peak of the Mn 2p spectrum centered at 640.9 eV can be attributed to the Mn 2p 3/2 , which is in good agreement with the binding energy of MnO [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The shoulder of Zn 2p in Figure 5 c is centered at 1019.27 eV and can be associated with the Zn broken bonds or O vacancies [ 39 , 40 ]. Additionally, the peak at 139.6 eV appearing in the Gd 4d spectra can be ascribed to the Gd4d 5/2 , showing that the oxidation state of Gd ions in the NPs is +3, which exist in the form of Gd 2 O 3 [ 41 ]. The detectable peak of the Mn 2p spectrum centered at 640.9 eV can be attributed to the Mn 2p 3/2 , which is in good agreement with the binding energy of MnO [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, some of the cations in Gd 2 O 3 are defective in nature and can absorb the radiation of UV spectral region and transfer the energy to the Er 3+ dopants with their following visible PL‐emission. It should be also noted, that such “defective” Gd 3+ ions with intracenter excitation and emission bands were also detected in undoped (pure) Gd 2 O 3 matrix . Defects of cationic and anionic sublattices of Gd 2 O 3 matrix are formed at the stage of nanoparticles synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…X‐ray photoelectron spectroscopy measurements were carried out using Thermo Scientific™ K‐Alpha + ™ XPS spectrometer under monochromatic X‐ray Al K α excitation in an oil‐free vacuum at 5 × 10 −6 Pa pressure. Figure shows XPS valence band spectra for cubic and monoclinic Gd 2 O 3 as well as reference spectrum for the nearly metallic Gd‐O x ( x = 0.9 at.%) . For the samples under study, we observed a complex pattern with a number of overlapping bands.…”
Section: Samples and Attestationmentioning
confidence: 99%
“…DFT calculations were performed using of the SIESTA pseudopotential code, a technique that has been recently successful in related studies of impurities in SiO 2 and gadolinium oxide . All calculations were made employing the generalized gradient approximation (GGA‐PBE) for the exchange‐correlation potential in a spin‐polarized mode.…”
Section: Methodsmentioning
confidence: 99%
“…Recent theoretical calculations demonstrate that pseudopotential methods provide good agreement with experiment for bulk Gd 2 O 3 and use of full potential methods does not strictly require. Our previous works in the area of oxides doped by transitional metals and gadolinium oxide demonstrate that using of DFT + U methods is not required for these systems. The cause of this is the strong crystal field acting on defects as in gadolinium impurities and on gadolinium oxide nanoparticles and gadolinium defects in semiconductors in contrast to bulk gadolinium oxide .…”
Section: Methodsmentioning
confidence: 99%